Take the Initiative, Stop Being Passive to NCDs: A PCA-Weighted Composite Indicator towards Prevalence of NCDs in Malaysia - Lee, Grace Chee-Yao; Wong, Shirly Siew-Ling; Puah, Chin-Hong (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In today’s highly dynamic socio-economic environment, the high degree of non-communicable diseases (NCDs) poses both direct and indirect health problems for nations. This study constructed a composite Non-Communicable Diseases Risk Indicator (NCDRI) that comprises leading characteristics to predict the movement of NCDs’ prevalence, which serves as an early signaling tool for policymakers and public health sectors. A weighting scheme for both non-weighted and principal component analysis (PCA)-weighted was applied from the PCA loading factor. The findings verified that the constructed PCA-weighted approach had a remarkable lead time, which also produced better lead times and was consistent in predicting the direction of change in the fluctuations caused by NCDs’ prevalence. An appropriate regime for policymaking and implementation is required, followed by periodic monitoring and rapid action, to reduce the deadly diseases. The findings of this study demonstrate that the cost indicator marked the most significant risk factor to indicate the prevalence of NCDs; therefore, policymakers should converge on this indicator so that cost-effective interventions can result in more valuable outcomes.